2018
DOI: 10.1007/s10905-018-9674-0
|View full text |Cite
|
Sign up to set email alerts
|

Trapping for Sirex Woodwasp in Brazilian Pine Plantations: Lure, Trap Type and Height of Deployment

Abstract: The Sirex woodwasp, Sirex noctilio (Hymenoptera: Siricidae) is considered a secondary pest of pine in its native range but has caused considerable economic losses in pine plantation forests in the southern hemisphere. In Brazil, trap trees are the primary tool used for early detection purposes but these are costly, labor-intensive to install and require stressing trees by herbicide application. Flight intercept traps baited with synthetic blends of host volatiles are an attractive alternative but have performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Concerning the distribution of S. noctilio in China, Carnegie 46 and Ireland 18 predicted that the regions from the northeast of Heilongjiang Province to the southwestern Yunnan Province (including the four areas evaluated in the current study) are climatically favorable for the establishment and persistence of S. noctilio , with all distribution records pointing to areas projected to be of moderate and high climatic suitability. Comparing the physical and chemical properties of host tree species in different areas invaded by S. noctilio , there is no obvious common characteristic 47 , 48 . P. taeda and P. elliottii are the host species of wasps in Canada and Brazil, and they are also distributed in the southern China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the distribution of S. noctilio in China, Carnegie 46 and Ireland 18 predicted that the regions from the northeast of Heilongjiang Province to the southwestern Yunnan Province (including the four areas evaluated in the current study) are climatically favorable for the establishment and persistence of S. noctilio , with all distribution records pointing to areas projected to be of moderate and high climatic suitability. Comparing the physical and chemical properties of host tree species in different areas invaded by S. noctilio , there is no obvious common characteristic 47 , 48 . P. taeda and P. elliottii are the host species of wasps in Canada and Brazil, and they are also distributed in the southern China.…”
Section: Discussionmentioning
confidence: 99%
“…mongolica , with gradual spreading to middle and southern China. The suitable hosts may encourage the spread of S. noctilio throughout China 46 , 48 . Pinus tabulaeformis is mainly distributed in the central regions and of China and, hence, it may be at a high risk of being attacked by S. noctilio .…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] Some of these rather ubiquitous compounds (e.g., ⊍ pinene and ⊎ pinene) are used to monitor and control female wasp populations in affected areas. [37][38][39][40][41] Recently, female responses towards other sources have been investigated. For instance, Cooperband et al 42 identified a close-range pheromone produced by males that is behaviourally-active in both females and males in laboratory trials, but not in the field.…”
Section: Introductionmentioning
confidence: 99%
“…At present, plant volatile compounds baited with black panel or multiple-funnel traps are the dominant traps used for detecting and monitoring S. noctilio . However, these traps have relatively good effects with moderate to large populations, but are ineffective with small populations, especially in environments with competitive volatiles produced by the host [ 53 ]. Finally, females carry arthrospores of a specific fungus, Amylostereum areolatum , in specialized internal organs called mycangia.…”
Section: Introductionmentioning
confidence: 99%